2015
DOI: 10.1111/exd.12586
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside F1 attenuates hyperpigmentation in B16F10 melanoma cells by inducing dendrite retraction and activating Rho signalling

Abstract: Ginsenoside F1 (GF1) is a metabolite produced by hydrolysis of the ginsenoside Re and Rg1 in Panax ginseng. According to various studies, high amounts of ginseng components are absorbed in the metabolized form, which are key constituents responsible for the biological effects of P. ginseng. Recently, GF1 was reported to have beneficial effects on skin. However, there has not been a sound understanding of its antimelanogenic effect and underlying molecular mechanisms. In this study, GF1 reduced a-melanocyte-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…After treatment with melanogenic compounds, B16F10 cells are known to increase secretion of melanin into the culture media [15]. It was observed that compound 1 treatment increased melanin secretion by the melanocytes (Figure 3(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After treatment with melanogenic compounds, B16F10 cells are known to increase secretion of melanin into the culture media [15]. It was observed that compound 1 treatment increased melanin secretion by the melanocytes (Figure 3(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previously published protocol [15]. B16F10 melanocytes were seeded in a 24-well plate at a density of 5 × 10 4 cells/well using 500  μ L culture media.…”
Section: Methodsmentioning
confidence: 99%
“…Ginsenoside F1 (GF1) is a metabolite produced by hydrolysis of the ginsenosides Re and Rg1 ( Kim et al, 2012 ). According to recent studies, GF1 exerts strong anti-aging, anti-oxidation, anticancer effects ( Kim et al, 2015 ). Moreover, it is exciting that we could obtain abundant GF1 through ginsenoside Rg1 bioconversion, which promotes the study of GF1 ( Kim et al, 2012 ; Wang Y. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 However, there are a few reports indicating that PPT-type ginsenosides inhibit melanin synthesis in melanocytes, although ginsenoside F1, a PPT-type ginsenoside, has been shown to exert a skin-whitening effect through dendrite retraction. 9 The present study provides the first demonstration that 20(S)-PPT appears to exert antimelanogenic effects through suppression of the pCREB-MITF-tyrosinase signalling pathway in melanocytes. Thus, PPT-type ginsenosides, in addition to the PPDtype, are potent whitening components of ginseng.…”
Section: Reportmentioning
confidence: 55%